Design Thinking Model as Inducer of Business Innovation: An Empirical Study - Bonini, Luiz Alberto (2011)
Nowadays innovation is one of the most important strategic drivers for organizations, as in 1970’sand in 1980’s the corporations were focused on total quality and in 1990’s on reengineering. Forcreating sustainable leadership in the future, organizations should: change the engagement rules in atraditional industry; redefine the boundaries between industries; and create entirely new sectors.However, the company’s predictive capability to change the sector arises when senior executivescan empathize with the basic human needs.In this context, the Design Thinking emerges as a model of innovation with high potential togenerate outstanding results for organizations seeking the leadership, since it contemplates methodsof research and development of solutions highly-focused on users. The aim of this study is toexplore the model of Design Thinking from the perspective of innovation strategic management.Therefore, the study includes literature searches on innovation, design and Design Thinking, asurvey with professionals who have experience applying the model and, finally, a case study of aBrazilian computer manufacturer.The results obtained demonstrate that the implementation of a systematized model of Design Thinking requires several cultural and process changes. However, the model is able to generatepositive results in the development of innovative solutions, since it is supported by advancedmethods to understand the context and to generate ideas focused on users and their needs.